Effects of decarbonation on elemental behaviors during subduction-zone metamorphism: Evidence from a titanite-rich contact between eclogite-facies marble and omphacitite. (March 2017) - Xiao, Yuanyuan; Niu, Yaoling; Zhang, Hong-Fu; Wang, Kuo-Lung; Iizuka, Yoshiyuki; Lin, Jinyan; Tan, Yulong; Xu, Yongjiang
Graphical abstract: Highlights: Omphacite and garnet indicate marble has experienced eclogite-facies metamorphism. Effects of carbonate subduction on element behaviors during SZM are discussed. Carbonate subduction is crucial for arc magmatism and mantle isotopic heterogeneity. Abstract: In this paper, we show the effects of subducted carbonates on geochemical processes during subduction-zone metamorphism (SZM) through the study of an eclogite-facies marble coexisting with metabasite from the ultrahigh pressure metamorphic belt of the Chinese Western Tianshan orogen. Between the marble and metabasite is a titanite-rich contact resulting from fluid-facilitated metamorphic reactions between the two lithologies, and recording elemental changes of geodynamic significance. Because this titanite-rich contact is dominated by titanite (an important host for high field strength elements, HFSEs) without white micas (an important host for large ion lithophile elements, LILEs), HFSEs are largely conserved in titanite whereas LILEs are moved away. This observation emphasizes the potential significance of subducting carbonate in retaining HFSEs in the slab through the formation and stabilization of titanite, contributing to the characteristic "arc signature" unique to subduction-zone magmatism (i.e., high LILEs, low HFSEs). The implicit assumption in this interpretation is that the observed lithological assemblage represents residues of subducting oceanic crust that has undergone major episodes of dehydration. Subducted carbonates also have significant implications for the origin of mantle isotopic heterogeneity as revealed from oceanic basalts.